STUDY OF FACIAL NERVE COURSE AND ITS VARIATION IN TEMPORAL BONE DISSECTION - KUMAR, ABHAY; CHAUHAN, JITENDRA PRATAP SINGH; TRIPATHI, AMRITA; DUBEY, SANTOSH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: There are various anatomical variations of the facial nerve in the bony canal making it prone to injury during mastoid surgeries. The objective of the present study is to find the course of the facial nerve and its variation in 40 cases of temporal bone dissection and to evaluate various parameters of the tympanomastoid segments of the facial nerve and its relation with the important middle ear structures. Methods: The present study was conducted in the Department of Otolaryngology, Uttar Pradesh University of Medical Sciences, Saifai, Etawah, on 40 temporal bones from January 2022 to December 2022. Various parameters of the tympanomastoid segments of the facial nerve and its relations with the important middle ear structures were studied in the present study. Results: In the present study, out of 40 bones dissected, 34 bones (85%) were well pneumatized whereas 6 bones (15%) were sclerotic in nature. In the present study, tympanic segment length varied from 7.65 to 11.72 mm with a mean of 9.32 mm (±1.02 mm). Vertical segment length varied from 10.2 to 15.9 mm with a mean of 13.48 mm (±1.21 mm). The distance of the second genu from the outer cortex varied from 17.67 to 23.71 mm with a mean of 19.73 mm (±1.44 mm). The distance of chorda tympani from stylomastoid foramen varied from 3.2 to 7.6 mm with a mean of 5.54 mm (±1.41 mm). Conclusion: Anatomical knowledge of facial nerve in the canal and its relation to surrounding structures is very helpful for ENT surgeons to avoid injury to it during middle ear surgeries.